“Forget About It”:“Parallel Processing” in the Srebrenica Report. - Runia, Eelco (History & Theory, 2004)
Dominick LaCapra has remarked that ‘when you study something, you always have a tendency to repeat the problems you are studying.’ In psychoanalytic supervision this phenomenon is called ‘parallel processing.’ Parallel processes are subconscious re-enactments of past events: when you are caught up in a parallel process, your behavior repeats key aspects of what there is to know about what you're studying—in a way, however, that you yourself don't understand. This article analyzes the extent to which the ‘NIOD Report,’ the official Dutch report on the massacre in Srebrenica (1995), ‘parallels’ the events it describes. It introduces the phenomenon, examines the way the NIOD researchers unwittingly replicated several key aspects of the events they studied, and discusses some instances in which parallelling highlights precisely those features of the events under consideration that are ham to come to terms with.